Answer: (3, -3)
=====================================================
Work Shown:
Add the x coordinates: 2+4 = 6
Divide that sum over two: 6/2 = 3
The x coordinate of the midpoint is x = 3
---------
Repeat those steps for the y coordinates
Add: -7+1 = -6
Divide in half: -6/2 = -3
The y coordinate of the midpoint is y = -3
----------
Overall, the midpoint is (3, -3)
The midpoint formula is
![\left(x_m, y_m\right) = \left((x_1+x_2)/(2),(y_1+y_2)/(2)\right)](https://img.qammunity.org/2021/formulas/mathematics/high-school/jnr5xnvu924z4ro1wh0bpw4y152d14z11u.png)